If Nobody Hears Us, Do We Really Make a Sound? Investigating Agriculture Faculty Members’ Engagement in Science Communication - Shelli D. Rampold; Taylor Ruth; Jamie Greig (Journal of Applied Communications, 2024)
Science communication is a crucial factor for ensuring scientific work in food and agriculture reaches intended end-users. Unfortunately, research faculty may not be willing or able to engage in science communication activities. This study was organized using the Faculty Engagement Framework to evaluate the personal, professional, and institutional factors that influence University of Tennessee faculty members’ engagement in public-facing science communication. Results indicated faculty members in this study were overall not highly engaged in science communication activities. Factors that significantly predicted their degree of engagement included knowledge of and attitudes toward communicating their science to public audiences. While the results of this study provide valuable insight for future training design and support measures to enhance faculty members’ engagement, further research with a larger sample size at multiple institutes is needed to better evaluate the relationship between the variables proposed in the model of the current study.
Keywords: Environmental communication; professionalism; professional development and training in science communication; scholarly communication